Blood mineral profile of normal cyclic and repeat breeder crossbred cows under rural condition - DAS, S; BANDOPADHYA, S K; BASU, S; GHOSH, B B; DAITAGUPTA, R (The Indian Journal of Animal Reproduction, 2023)
The serum calcium. inorganic phosphorus, copper, zinc. iron and maganese were estimated in 22 repeat breeder and 12 normal cyclic crossbred cows. Repeat breeder cows had significantly lower inorganic P (4.729±0.150 mg; I 00 ml), Cu (0.96±0.017 μg, ml) and Zn ( 1.80±0.033 μg/ml) than normal cyclic cows where the levels were 5.513±0.265 mg/ I 00 ml, 0.97±0.023 μg/ml and 2.09±0.057 μg/ml , respectively. Higher serum iorn level was found in the repeat breeders (3.594±0.043 μg,1ml) than normal cyclic cows (3.424±0.053 μg/ml). No significant variation however. was found in Ca and Mn between the groups.